2017
DOI: 10.15740/has/au/12.techsear(6)2017/1573-1577
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability analysis for yield and related traits in rice (Oryza sativa L.)

Abstract: Study of combining ability was conducted on 12 F 1 hybrids along with seven rice genotypes to know the pattern of inheritance of some morphological traits for selecting superior genotypes. The experiment was carried out and crossing programme initiated in line x tester mating design during Post rainy season 2013-14 and subsequently hybrids along parents were evaluated during rainy season 2014. Analysis of variance for combining ability revealed highly significant mean square for all the characters due to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…,Pradhan et al (2006),Rashid et al (2007),Saleem et al (2010) andSaidaiah et al (2010).The traits with non-additive gene action can be further subjected to heterosis breeding. Many researchersSaidaiah et al (2010),Singh et al (2020) andSandhyakishore et al (2017) have reported the predominance of non-additive gene action for the above-mentioned traits. In the case of additive gene action,Widyastuti et al (2017) andZewdu et al (2020) suggested pureline selection or pedigree breeding improve the traits.…”
mentioning
confidence: 99%
“…,Pradhan et al (2006),Rashid et al (2007),Saleem et al (2010) andSaidaiah et al (2010).The traits with non-additive gene action can be further subjected to heterosis breeding. Many researchersSaidaiah et al (2010),Singh et al (2020) andSandhyakishore et al (2017) have reported the predominance of non-additive gene action for the above-mentioned traits. In the case of additive gene action,Widyastuti et al (2017) andZewdu et al (2020) suggested pureline selection or pedigree breeding improve the traits.…”
mentioning
confidence: 99%